2008
DOI: 10.1371/journal.pntd.0000272
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Variability of Dengue Virus Proteins: Implications for Vaccine Design

Abstract: BackgroundGenetic variation and rapid evolution are hallmarks of RNA viruses, the result of high mutation rates in RNA replication and selection of mutants that enhance viral adaptation, including the escape from host immune responses. Variability is uneven across the genome because mutations resulting in a deleterious effect on viral fitness are restricted. RNA viruses are thus marked by protein sites permissive to multiple mutations and sites critical to viral structure-function that are evolutionarily robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 82 publications
6
110
1
Order By: Relevance
“…The evolutionary conservation and variability of the identified T-cell ligand regions in the alignments of the recorded WNV sequences were measured by use of a modified Shannon's entropy computation function (16,56) in the Antigenic Variability Analyzer (AVANA) software (http://sourceforge.net /projects/avana/) (33). The entropy of a ligand sequence (15 to 19 aa) position in the alignment was measured as the average of the entropies of the (7 to 11) nonamer positions within the ligand sequence position.…”
Section: Methodsmentioning
confidence: 99%
“…The evolutionary conservation and variability of the identified T-cell ligand regions in the alignments of the recorded WNV sequences were measured by use of a modified Shannon's entropy computation function (16,56) in the Antigenic Variability Analyzer (AVANA) software (http://sourceforge.net /projects/avana/) (33). The entropy of a ligand sequence (15 to 19 aa) position in the alignment was measured as the average of the entropies of the (7 to 11) nonamer positions within the ligand sequence position.…”
Section: Methodsmentioning
confidence: 99%
“…We also demonstrated that maternal antibodies inhibit seroconversion upon PDK53 vaccination in pups born to PDK53-immune dams. However, we hypothesized that vaccination of these pups with PDK53 may still induce T cell-mediated protection, which usually targets the more conserved nonstructural proteins (17,18,38,39). It was indeed reported that the T cell response to vaccination was not impaired by maternal antibodies (29).…”
Section: Pdk53 Vaccination Protected Against D2y98p-pp1 In the Contexmentioning
confidence: 98%
“…A number of DENV specific T cell activating epitopes have been reported; 4,5,[28][29][30] however, these epitopes have been generated using peptide prediction algorithms and therefore may not accurately represent the natural peptides presented on MHC class I molecules of the infected cells. In addition, in order for a vaccine formulation to be universally applicable (i.e.…”
Section: Identification Of Dengue Virus Specific T Cell Epitopes By Nmentioning
confidence: 99%